2004
DOI: 10.1021/bp0343211
|View full text |Cite
|
Sign up to set email alerts
|

HPCE Monitoring of the N-Glycosylation Pattern and Sialylation of Murine Erythropoietin Produced by CHO Cells in Batch Processes

Abstract: Using capillary electrophoresis coupled to laser-induced fluorescence (HPCE-LIF), it was possible to profile N-linked oligosaccharides from EPO, including species containing sialic acid, during the course of batch cultures performed either in serum-free or serum-containing medium. Although an unusual high heterogeneity of the N-linked oligosaccharides was observed by both SDS-PAGE and HPCE analysis, the patterns of mEPO glycans after desialylation by mild acid hydrolysis were found to be quite constant over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…4c). As already published (Le Floch et al 2004) the EPO glycosylation patterns determined all over the process were very similar to those of EPO collected at the beginning of the previous culture meaning that desialylation observed in the previous experiment did not occur for these serum-free conditions using adapted cells. In addition to the previously published results, we performed analysis of EPO glycans collected at the end of the cell growth phase and at the end of the culture (after 100 and 260 h) in presence of serum, but with cells previously adapted to serum-free conditions (culture #2).…”
Section: Kinetics Of Cells Adapted and Non-adapted To Serum-free Condsupporting
confidence: 81%
See 4 more Smart Citations
“…4c). As already published (Le Floch et al 2004) the EPO glycosylation patterns determined all over the process were very similar to those of EPO collected at the beginning of the previous culture meaning that desialylation observed in the previous experiment did not occur for these serum-free conditions using adapted cells. In addition to the previously published results, we performed analysis of EPO glycans collected at the end of the cell growth phase and at the end of the culture (after 100 and 260 h) in presence of serum, but with cells previously adapted to serum-free conditions (culture #2).…”
Section: Kinetics Of Cells Adapted and Non-adapted To Serum-free Condsupporting
confidence: 81%
“…Figure 4a presents the HPCE patterns of complete and desialylated N-glycans of EPO produced at the beginning and at the end of the culture (after 40 and 300 h) performed in presence of serum, with the non-adapted cells (culture #1). As shown already (Le Floch et al 2004), the HPCE patterns of non-desialylated and chemically desialylated N-glycans from EPO revealed that, except for the sialylation degree, glycosylation of EPO was quite constant all over the culture.…”
Section: Kinetics Of Cells Adapted and Non-adapted To Serum-free Condsupporting
confidence: 63%
See 3 more Smart Citations